(untitled) (Journal of Student Affairs in Africa, 2021)
“Under-preparedness” of students entering higher education is an issue that many academic institutions in South Africa are currently trying to address. Such students are seen as disadvantaged, lacking the skills, knowledge and/or language proficiency to navigate their way to success in higher education. This paper seeks to identify students’ understanding of the behaviour they should display in higher education and how this clashes with the expectations of academics, through the lenses of different discourses and academic literacy models. Specifically, the focus is on how students try to engage with the institutional discourse and how they try to identify a “sense of being” through a case study of the Extended Curriculum Programme in Nature Conservation at the Cape Peninsula University of Technology. Here, qualitative research was used through the administration of student essays, as well as individual face-to-face interviews. Lecturers were also interviewed so that a comparison could be made between what students perceive and the expectations of higher education. Different themes were identified through the analysis of the data, using an inductive approach; by developing the themes, the gaps are better identified and analysed with a view to redress.